2021
DOI: 10.1186/s12978-021-01152-5
|View full text |Cite
|
Sign up to set email alerts
|

“I came to escort someone”: Men’s experiences of antenatal care services in urban Ghana—a qualitative study

Abstract: Background Male involvement in maternal healthcare has been widely recognized as essential for positive health outcomes for expectant mothers and their unborn babies. However, few studies have explored men’s experiences of maternal health services. The purpose of this paper is to explore men’s involvement in antenatal care in urban Ghana and to discuss how men navigate their roles in a space that has been constructed as feminine. The study draws upon theories of space, place, and gender. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Further, the increased likelihood of wanting to consult for decisions with mothers, male partners, sisters and other family members implies maternity care needs to expand access to a variety of other support persons. Literature and health policies have predominantly focused on male partner involvement and providers frequently give preferential treatment to male partners [ 8 , 33 , 41 – 44 ]. Yet, many studies have found preferences for mothers and other female relatives, often stemming from cultural preferences [ 12 , 22 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the increased likelihood of wanting to consult for decisions with mothers, male partners, sisters and other family members implies maternity care needs to expand access to a variety of other support persons. Literature and health policies have predominantly focused on male partner involvement and providers frequently give preferential treatment to male partners [ 8 , 33 , 41 – 44 ]. Yet, many studies have found preferences for mothers and other female relatives, often stemming from cultural preferences [ 12 , 22 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Provision of information and education facilitates support persons’ involvement in care and clarifies their roles [ 16 , 30 32 ]. The ability to ask questions and express concerns acknowledges the importance of engagement with providers during care, especially as an avenue to advocate on behalf of the supported women [ 13 , 16 , 23 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lack of significance of male partners' gender-equitable attitudes and behaviors as predictors of the FTM's completion of the MH continuum of care may be partly explained by the fact that men may generally feel disengaged and out of place at maternal healthcare services; and may be physically distanced outside the clinic. Even though men tend to be the primary decision makers for women's access to care, prevailing sociocultural norms defining pregnancy and childbirth as women's spaces may leave men disempowered and spatially and socially marginalized in maternal healthcare settings [61]. However, the low concordance between FTMs and male partners reports of joint decision making suggests that further research is needed to better understand effective couple communication and couples' interpretation of each other's role in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…In areas where ambulances do not have access due to a lack of roads, providing villagers with practical means of transportation such as bicycles or donkey carts, according to the characteristics of the terrain, would enable villagers not only to cope with maternal emergency situations but also to receive appropriate ANC [ 8 ]. Lastly, in the case of men accompanying their wives to a medical facility, in many cases they are required to remain in the waiting area and choose an isolated place outside the medical facility until the treatment is completed [ 28 ]. In addition, the attitude of medical staff who fail to encourage male participation in the ANC process is perceived as a negative experience, which reduces active participation among men [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for women with limited social relationships, the space for receiving prenatal care needs to be not just a physical place but a space in which they can form social relationships with other pregnant women and share reproductive health information. Therefore, changes in social norms are necessary to enhance women’s autonomy and to recognise that the medical waiting space is a space that includes men, not just women [ 28 ].…”
Section: Discussionmentioning
confidence: 99%